MODELING AND SIMULATION OF FLUID FLOWDYNAMICS FOR CO₂ MIGRATION IN TWO-DIMENSIONAL SALINE AQUIFERS - Henglai Zhai; Zaibin Lin; Francisco Bruno Souza Oliveira; Jefferson Gomes (Vetor)
Geological carbon sequestration is increasingly recognized as a promising solution for mitigating CO2 emissions by storing CO2 in geological formations such as saline aquifers. Although recent research has primarily focused on optimizing CO2 trapping mechanisms to enhance storage efficiency, the flow dynamics of CO2 plume migration—particularly the propagation and growth of fingers—remain insufficiently understood. In response to these challenges, we develop a model to simulate CO2 plume migration in both homogeneous and heterogeneous porous media within two-dimensional (2D) saline aquifers. This study utilizes high-order reservoir simulations within the ICFERST framework, employing the control volume finite element method (CVFEM) to specifically capture the viscous instabilities associated with CO2 plume migration. The simulation process integrates various mesh resolutions and incorporates adaptive mesh optimization (AMO). Our results indicate that increasing mesh resolution significantly enhances the ability to accurately capture the formation and growth of CO2 fingers. In homogeneous porous media, AMO effectively balances accuracy and computational efficiency by dynamically refining or coarsening the mesh in critical regions. In heterogeneous porous media, simulations reveal the emergence of wider and larger fingers compared to those observed in homogeneous settings, with bifurcations occurring at locations where relative permeability undergoes significant changes.